Comparison of different cytogenetic methods and tissue suitability for the study of chromosomes in Cimex lectularius (Heteroptera, Cimicidae) - Sadílek, David; Angus, Robert B; Šťáhlavský, František; Vilímová, Jitka (Comparative cytogenetics, 2016)
In the article we summarize the most common recent cytogenetic methods used in analysis of karyotypes in Heteroptera. We seek to show the pros and cons of the spreading method compared with the traditional squashing method. We discuss the suitability of gonad, midgut and embryo tissue in Cimex lectularius Linnaeus, 1758 chromosome research and production of figures of whole mitosis and meiosis, using the spreading method. The hotplate spreading technique has many advantages in comparison with the squashing technique. Chromosomal slides prepared from the testes tissue gave the best results, tissues of eggs and midgut epithelium are not suitable. Metaphase II is the only division phase in which sex chromosomes can be clearly distinguished. Chromosome number determination is easy during metaphase I and metaphase II. Spreading of gonad tissue is a suitable method for the cytogenetic analysis of holokinetic chromosomes of Cimex lectularius.
Keywords: midgut; squashing method; testes; spreading method; karyogram; holokinetic chromosomes